Penyakit Orf Pada Kambing (Studi Kasus di CV Mitra Farm, Bogor, Jawa Barat) - N Kotimah; N Irwani; K Magfiroh (PETERPAN (Jurnal Peternakan Terapan), 2019)
Goats are livestock that is classified as small ruminants. One of the factors that influence goat productivity is health management. Health management is a disease control process so that livestock productivity can be maximized. One of the goat diseases in CV Mitra Tani Farm is an 'orf' disease. "Orf" is a scab that attacks the area around the goat's mouth. The ‘orf’ disease is caused by a zoonotic virus. Orf can cause goats to have difficulty in consuming food, so that the goats become thin, and increase morbidity. The purpose of this Final Project was to determine the occurrence of 'orf' disease in goats in CV Mitra Tani Farm. PE goats and pea goats were used as observation material. Observation, interviews, and secondary data collection were used to collect data in the CV. Mitra Tani Farm. Based on the observations of ‘orf’ disease in CV Mitra Tani Farm can be concluded that the clinical symptoms seen are blisters in the area around the mouth on the edge of the right lip. Orf disease management in the CV. Mitra Tani Farm was cleaning scabs around the mouth and administration of drugs in the form of gusanex® and vitamin B-complex. Keywords: Goat, orf disease, management